Collective action in a tropical estuarine lagoon: adapting Ostrom's SES framework to Ciénaga Grande de Santa Marta, Colombia. Issue 1 (February 2016) - Torres Guevara, Luz Elba; Schlüter, Achim; Lopez, Maria Claudia
The paper contributes to the social-ecological systems literature by adapting and using Elinor Ostrom's Social-Ecological System (SES) framework in the context of a coastal ecosystem. We modified the SES framework in the case of the Ciénaga Grande de Santa Marta (CGSM), an estuarine lagoon in the Caribbean coast of Colombia. The ecological importance of CGSM and its species is undeniable. This paper aims to understand why collective action for a sustainable use of CGSM's fishery resources has not taken place. In order to respond to that question, we created new variables within the social, economic, and political settings of the SES framework. The results show that the fishers' fear of the indiscriminate and strong violence that illegal armed groups have inflicted on them since the 1960s and the economic development in the Colombian Caribbean region help explain the lack of collective action.